Correction to "Benefits of Ion Mobility Separation and Parallel Accumulation-Serial Fragmentation Technology on timsTOF Pro for the Needs of Fast Photochemical Oxidation of Protein Analysis" - Loginov, Dmitry S; Fiala, Jan; Chmelik, Josef; Brechlin, Peter; Kruppa, Gary; Novak, Petr (ACS omega, 2021)
[This corrects the article DOI: 10.1021/acsomega.1c00732.].